O ensino de história nos museus paulistas, uma proposta pedagógica a partir do projeto Lugares de Aprender da Fundação para o Desenvolvimento da Educação (FDE) - Barbosa, Moroni Tartalioni (2010)
This work aims at analyzing one out of three projects from the program named Cultura é Currículo (Culture is Curriculum): the project Lugares de Aprender (Places to Learn), elaborated according to the curricular guideline proposed by the Education State Secretary of Sao Paulo, in 2008. We tried to comprehend, by investigating the material proposed by the project Lugares de Aprender, which contents and methodologies were offered to Elementary School teachers, in order to guide their educational relations with museums. We have established as a criterion for examining the material aspects related to contents and materiality. Besides the analysis of the material, we tried to comprehend the communication lines and the implementation of the project, which was realized from institutional reports exams provided by FDE. The aim of this procedure was to check the teachers practices with museums and detach the participation of different agents on the achievement of the main objective detached with this project: the colligation between school and culture